2010
DOI: 10.2139/ssrn.1726022
|View full text |Cite
|
Sign up to set email alerts
|

Too Small or Too Low? New Evidence on the 4-Factor Model

Abstract: Copyright belongs to the author. Small sections of the text, not exceeding three paragraphs, can be used provided proper acknowledgement is given. The Rimini Centre for Economic Analysis (RCEA) was established in March 2007. RCEA is a private, nonprofit organization dedicated to independent research in Applied and Theoretical Economics and related fields. RCEA organizes seminars and workshops, sponsors a general interest journal The Review of Economic Analysis, and organizes a biennial conference: The Rimini C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In many studies done with regard to developed markets, though the R 2 and GRS F-statistic improve when moving from CAPM to the four-factor model (through the three-factor model), they reject the four-factor model based on the GRS F-test. In addition, Brighi et al (2010) find that adding the momentum factor does not improve the performance of the three-factor model in its application in the Milan Stock Exchange. Looking at developing markets, Hasnaoui and Ibrahim (2013) accept the four-factor model and reject the three-factor model based on the GRS F-test for their study done on the Tunis Stock Exchange; Unlu (2013) accepts both the three-factor model and four-factor model for the Istanbul Stock Exchange based on the GRS F-test.…”
Section: Asset Pricing Testsmentioning
confidence: 89%
See 1 more Smart Citation
“…In many studies done with regard to developed markets, though the R 2 and GRS F-statistic improve when moving from CAPM to the four-factor model (through the three-factor model), they reject the four-factor model based on the GRS F-test. In addition, Brighi et al (2010) find that adding the momentum factor does not improve the performance of the three-factor model in its application in the Milan Stock Exchange. Looking at developing markets, Hasnaoui and Ibrahim (2013) accept the four-factor model and reject the three-factor model based on the GRS F-test for their study done on the Tunis Stock Exchange; Unlu (2013) accepts both the three-factor model and four-factor model for the Istanbul Stock Exchange based on the GRS F-test.…”
Section: Asset Pricing Testsmentioning
confidence: 89%
“…In terms of its explanatory power, the four-factor model performs better than the Fama and French (1993) three-factor model in developed markets; however, in terms of the GRS F-test the results are not consistent in rendering regressions where the true intercepts are jointly zero (Bello, 2008;Brighi et al, 2010;Fama and French, 2012;Humphrey and O'Brien, 2010). Conversely when the GRS F-test is applied to emerging and developing markets the four-factor model is found to be more successful (Nartea et al, 2009;Lam et al, 2009;Lai and Lau, 2010;Cakici et al, 2013;Unlu, 2013;Hasnaoui and Ibrahim, 2013;Vo, 2015;Balakrishnan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inferior performance of the four-factor model is also being witnessed by Nartea et al (2009) in the New Zealand stock market. Similar evidence of the weaker performance of the fourfactor model was found in the Italian stock market by Brighi et al (2010). The period also witnessed the introduction of liquidity augmented three-factor model which is another effort being done (Chen et al, 2011) in the Chinese stock market wherein the results revealed the better explanatory power of the new four-factor model.…”
Section: Literature Reviewmentioning
confidence: 54%